The limitations of international humanitarian law to the reallocation of Iraqi oil resources under the US/UK transformative occupation of Iraq - Power, Susan Rose (Trinity College (Dublin, Ireland). School of Law, 2011)
This thesis examines the emergence of a new characterisation of belligerent occupation evidenced in Iraq (2003-2004), transformative belligerent occupation. After the institutions of government were destroyed in hostilties it was apparent that some form of state building exercise was necessary to transform the territory to restore order there. Consequently, the belligerent occupying powers were authorised by Security Council Resolution Chapter VII mandate to transform the territory and comply with their obligations under the Hague Regulations of 1907 and Geneva Conventions of 1949.
Keywords: Law, Ph.D.; Ph.D. Trinity College Dublin.